Reputation Risk Management Related To Animal Welfare at Taman Safari - Yohana Tri Hastuti; Siti Jahroh; Widodo Ramadyanto (Asian Journal of Social and Humanities, 2024)
Taman Safari as one of the educational tourist destinations has a big responsibility in maintaining the welfare of the animals in it. Animal welfare is an important factor that affects the reputation of conservation institutions, especially in the face of public and media scrutiny. This article aims to analyze the risk management related to animal welfare in Taman Safaris in order to minimize the potential negative impact on the reputation of the institution. Through a reputational risk analysis approach, the study identifies key risk factors such as the treatment of animals, maintenance facilities, and the transparency of information provided to the public. The results of the analysis show that mitigation strategies, such as the implementation of international animal welfare standards and the improvement of transparent communication, are essential to maintain the reputation of the Taman Safari in the eyes of the public. With effective risk management, Taman Safari can maintain its image as an institution that cares about animal conservation and welfare.